Penanaman Nilai Karakter Berbasis Kearifan Lokal dalam Pembelajaran IPS di MTs Sabilul Ulum Mayong - Arisatun Khoiryah (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2022)
The research conducted aims to determine (1) the character values ​​of students through the local wisdom of the community in Mayong Village, Jepara Regency. (2) Embedding local wisdom-based character values ​​in social studies learning at MTs Sabilul Ulum Mayong Jepara. (3) Obstacles experienced by teachers applying character values ​​in the social studies learning process at MTs Sabilul Ulum Mayong Jepara. This type of research is field research (field research) using a qualitative descriptive approach. The subjects of this study included social studies teachers, and class VII A students at MTs Sabilul Ulum Mayong. Research data sources are primary and secondary sources. Data search techniques were obtained by observation, interviews and documentation studies. All data was collected and then analyzed using Miles and Huberman's analysis. By collecting data, reducing data, presenting data and verifying data/drawing conclusions The results of this study indicate that: (1) There are two local wisdoms in the village of Mayong, Jepara Regency which can be used as learning references, such as clay crafts and the cultural carvings of Mrs. Mas Semangkin. Character values ​​that can be used as learning are: Historical Values, Economic Values, Mutual Cooperation Values, and Religious Values. (2) The implementation of instilling local wisdom-based character values in social studies learning in class VII A according to the RPP, namely initial activities, core activities, and closing activities. (3) Constraints experienced by teachers applying character values ​​in the social studies learning process, in the learning process there are 2 constraint factors, namely external and internal